Phylogenetic analysis of beak and feather disease virus across a host ring-species complex - Eastwood, Justin R. (National Academy of Sciences, 2014)
Pathogens have been hypothesized to play a major role in host diversity and speciation. Susceptibility of hybrid hosts to pathogens is thought to be a common phenomenon that could promote host population divergence and subsequently speciation. However, few studies have tested for pathogen infection across animal hybrid zones while testing for codivergence of the pathogens in the hybridizing host complex. Over 8 y, we studied natural infection by a rapidly evolving single-strand DNA virus, beak and feather diseases virus (BFDV), which infects parrots, exploiting a host-ring species complex (Platycercus elegans) in Australia. We found that host subspecies and their hybrids varied strikingly in both BFDV prevalence and load: both hybrid and phenotypically intermediate subspecies had lower prevalence and load compared with parental subspecies, while controlling for host age, sex, longitude and latitude, as well as temporal effects. We sequenced viral isolates throughout the range, which revealed patterns of genomic variation analogous to Mayr’s ring-species hypothesis, to our knowledge for the first time in any host–pathogen system. Viral phylogeny, geographic location, intraspecific host density, and parrot community diversity and composition did not explain the differences in BFDV prevalence or load between subpopulations. Overall, our analyses suggest that functional host responses to infection, or force of infection, differ between subspecies and hybrids. Our findings highlight the role of host hybridization and clines in altering host–pathogen interactions, dynamics that can have important implications for models of speciation with gene flow, and offer insights into how pathogens may adapt to diverging host populations.